Distinct T cell responsiveness to different COVID-19 vaccines and cross-reactivity to SARS-CoV-2 variants with age and CMV status - Brummelman, Jolanda; Suárez-Hernández, Sara; de Rond, Lia; Bogaard-van Maurik, Marjan; Molenaar, Petra; van Wijlen, Emma; Oomen, Debbie; Beckers, Lisa; Rots, Nynke Y.; van Beek, Josine; Nicolaie, Mioara A.; van Els, Cécile A. C. M.; et al. (Frontiers in Immunology, 2024)
Accumulating evidence indicates the importance of T cell immunity in vaccination-induced protection against severe COVID-19 disease, especially against SARS-CoV-2 Variants-of-Concern (VOCs) that more readily escape from recognition by neutralizing antibodies.However, there is limited knowledge on the T cell responses across different age groups and the impact of CMV status after primary and booster vaccination with different vaccine combinations. Moreover, it remains unclear whether age has an effect on the ability of T cells to cross-react against VOCs. Therefore, we interrogated the Spike-specific T cell responses in healthy adults of the Dutch population across different ages, whom received different vaccine types for the primary series and/or booster vaccination. Cells were stimulated with overlapping peptide pools of the ancestral Spike protein and different VOCs. Using an IFNɣ ELISpot, robust Spike-specific T cell responses were detected in the vast majority of participants upon the primary vaccination series, regardless of the vaccine type (i.e. BNT162b2, mRNA-1273, ChAdOx1 nCoV-1, or Ad26.COV2.S). Clearly, in the 70+ age group, responses were overall lower and showed more variation compared to younger age groups. Only in CMV-seropositive older adults (>70y) there was a significant inverse relation of age with T cell responses.Although T cell responses increased in all age groups after booster vaccination, Spike-specific T cell frequencies remained lower in the 70+ age group. Regardless of age or CMV status, primary mRNA-1273 vaccination followed by BNT162b2 booster vaccination showed limited booster effect compared to the BNT162b2/BNT162b2 or BNT162b/mRNA-1273 prime-boost regimen. A modest reduction in cross-reactivity to the Alpha, Delta and Omicron BA.1, but not the Beta or Gamma variant, was observed after primary vaccination. Together, this study shows that age, CMV status, but also the primary-booster vaccination regimen influence the height of the vaccination-induced Spike-specific T cell response, but did not impact the VOC cross-reactivity.